Nanoengineering of bioactive glasses: hollow and dense nanospheres - Luz, Gisela (2013)
The possibility of engineering bioactive glass (BG) nanoparticles into suitable sizes and shapes represents a significant achievement regarding the development of new osteoconductive biomaterials for therapeutic strategies to replace or regenerate damaged mineralised tissues. Hereinwe report the structural and chemical evolution of sol–gel derived BG nanoparticles for both the binary (SiO2:CaO (mol%) = 70:30) and ternary (SiO2:CaO:P2O5 (mol%) = 55:40:5) formulations, in order to understand how the particles formation can be directed. Hollow BG nanospheres were obtained through Ostwald ripening. The presence of a non ionic surfactant, poly(ethylene glycol) (PEG), allowed the formation of dense BG nanospheres with controllable diameters depending on the molecular weight of PEG. A deep insight into the genesis of BG nanoparticles formation is essential to design BG based materials with controlled compositions, morphologies and sizes at the nanoscale, in order to improve their performance in orthopaedic applications including bone tissue engineering.